Ethanol ablation for refractory bile leakage after complex hepatectomy. Issue 8 (4th April 2018) - Ito, A.; Ebata, T.; Yokoyama, Y.; Igami, T.; Mizuno, T.; Yamaguchi, J.; Onoe, S.; Nagino, M.
Abstract : Background: Only a few reports exist on the use of ethanol ablation for posthepatectomy bile leakage. The aim of this study was to assess the value of ethanol ablation in refractory bile leakage. Methods: Medical records of consecutive patients who underwent a first hepatobiliary resection with bilioenteric anastomosis between 2007 and 2016 were reviewed retrospectively, with special attention to bile leakage and ethanol ablation therapy. Bile leakage was graded as A/B1/B2 according to the International Study Group of Liver Surgery definition. Absolute ethanol was injected into the target bile duct during fistulography. Results: Of the 609 study patients, 237 (38·9 per cent) had bile leakage, including grade A in 33, grade B1 in 18 and grade B2 in 186. Left trisectionectomy was more often associated with grade B2 bile leakage than other types of hepatectomy ( P < 0·001). Of 186 patients with grade B2 bile leakage, 31 underwent ethanol ablation therapy. Ethanol ablation was started a median of 34 (range 15–122) days after hepatectomy. The median number of treatments was 3 (1–7), and the total amount of ethanol used was 15 (3–71) ml. Complications related to ethanol ablation included transient fever (27 patients) and mild pain (13). Following ethanol ablation, bile leakage resolved in all patients and drains were removed. The median interval between the first ablation and drain removal was 28 (1–154) days. Conclusion: Ethanol ablation is safe and effective, and may be a treatment option for refractory bile leakage. Abstract : Ethanol ablation is effective